Applicability of the CURB-65 pneumonia severity score for outpatient treatment of COVID-19. Issue 3 (September 2020) - Nguyen, Yann; Corre, Félix; Honsel, Vasco; Curac, Sonja; Zarrouk, Virginie; Fantin, Bruno; Galy, Adrien
Abstract: Objectives: The CURB-65 is a severity score to predict mortality secondary to community acquired pneumonia and is widely used to identify patients who can be managed as outpatients. However, whether CURB-65 can be applicable to COVID-19 patients for the decision of outpatient treatment is still unknown. Methods: We conducted a retrospective single-centre study assessing the performance of the CURB-65 to predict the risk of poor outcome, defined as the need for mechanical ventilation and/or death, among patients hospitalized for COVID-19. The association between the CURB-65 and the outcome was assessed by a univariable Cox proportional hazard regression model. Results: A total of 279 patients were hospitalized between March 15 th and April 14 th, 2020. According to the CURB-65, 171 (61.3%) patients were considered at low risk (CURB-65 01), 66 (23.7%) at intermediate risk (CURB-65=2), and 42 (15.1%) had high risk of 30-day mortality (CURB-65 35). During the study period, 88 (31.5%) patients had a poor outcome. The CURB-65 was strongly associated with a poor outcome ( Pfor linear trend <0.001). However, among patients with a CURB-65 of 01, thus considered at low risk, 36/171 (21.1%) had a poor outcome. Conclusions: Our study suggests that the applicability of CURB-65 to guide the decision of inpatient or outpatient care is scarce, as it does not safely identify patients who could be managed as outpatients.